Ответ: tg∠M=
Объяснение:
1) По теореме Пифагора имеем:
MN²-ND²=MD²
MD===
2) tg∠M=
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ: tg∠M=![\frac{9}{4\sqrt{10}} \frac{9}{4\sqrt{10}}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B4%5Csqrt%7B10%7D%7D)
Объяснение:
1) По теореме Пифагора имеем:
MN²-ND²=MD²
MD=
=
=![4\sqrt{10} 4\sqrt{10}](https://tex.z-dn.net/?f=4%5Csqrt%7B10%7D)
2) tg∠M=![\frac{9}{4\sqrt{10}} \frac{9}{4\sqrt{10}}](https://tex.z-dn.net/?f=%5Cfrac%7B9%7D%7B4%5Csqrt%7B10%7D%7D)